Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Câu 2: Vì a+b+c=6
=>(a+b+c)2=62=36
=>a2+b2+c2+2ab+2bc+2ac=36
=>2(ab+ac+bc)=24
=>ab+ac+bc=12
=>a2+b2+c2=ab+ac+bc
Mà a2+b2+c2>=ab+ac+bc.Dấu "=" xảy ra <=> a=b=c
Do đó a=b=c
Mà a+b+c=6
=>a=b=c=2
=>P=(2-3)2013 - (2-3)2013 - (2-3)2013 = - 1 - ( -1) - (-1)=1
Dễ chứng minh được \(a^2+b^2+c^2\ge\frac{\left(a+b+c\right)^2}{3}\)\(\)
\(\Leftrightarrow\left(a-b\right)^2+\left(b-c\right)^2+\left(c-a\right)^2\ge0\left(true\right)\)
\(\Rightarrow2\left(a+b+c\right)\ge\frac{\left(a+b+c\right)^2}{3}\)
\(\Leftrightarrow a+b+c\le6\)
Ta có : \(T=\frac{a}{a+1}+\frac{b}{b+1}+\frac{c}{c+1}\)
\(=1-\frac{1}{a+1}+1-\frac{1}{b+1}+1-\frac{1}{c+1}\)
\(=3-\left(\frac{1}{a+1}+\frac{1}{b+1}+\frac{1}{c+1}\right)\)
\(\le3-\frac{9}{a+b+c+3}\le3-\frac{9}{6+3}=2\)
Dấu "=" xảy ra khi \(a=b=c=2\)